Battle for christendom - Welsh, Frank ([S.l.] : Overlook Hardcover, 2008)
At the dawn of the fifteenth century, Islam invaded Europe from the East and it seemed that Christendom itself was under threat. In an attempt to save the Christian world, the Holy Roman Emperor Sigismund called a conference at Constance, beside the Rhine. The council attracted the greatest minds in the western world, as well as innumerable princes, lawyers, and prostitutes. In The Battle for Christendom , eminent historian Frank Welsh delves into this important incident and shows that it is in fact one of the central moments in European history. Schism had ravaged the Catholic Church and three Popes were claiming the seat of St. Peter's. The event would be a critical turning point in European history--the last event of the medieval world, heralding the dawn of the renaissance and the rise of humanism. Yet it would also hold a darker truth and with the burning of the Czech divine, Jan Hus, saw first moments of the Reformation. The story rises to a conclusion on the battlements of Constantinople in 1453 where, despite all of Sigismund's attempts to repel the Ottomans, Islam rose up once more. In Welsh's lively retelling, The Battle for Christendom is an exciting and readable story that holds lessons for our own times of international turmoil.